Marketing Development Strategy for Pasteurized Crab (Portunus pelagicus) Export Commodities at PT Jala Crabindo International - Aisyah Safitri; Migie Handayani; Dian Ayunita Nugraheni Nurmala Dewi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The export marketing of pasteurized blue swimming crab (Portunus pelagicus) is an important sector in Indonesia’s fisheries agribusiness; however, it faces challenges arising from global market competition and import tariff policies that affect product competitiveness. This study aims to analyze the internal and external factors influencing the export marketing of pasteurized blue swimming crab at PT Jala Crabindo International (JCI) and to formulate effective marketing strategies to enhance product competitiveness in international markets. The research was conducted at PT JCI, Semarang, using a quantitative approach with purposive sampling involving six key informants. Data were collected through interviews, observations, questionnaires, and literature reviews, and analyzed using SWOT analysis, the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, and the Analytical Hierarchy Process (AHP). The results indicate that PT JCI possesses strong internal advantages, including a strategic location near raw material sources, modern pasteurization technology, competent human resources, export quality certifications, and a stable supplier network. Nevertheless, the company faces several weaknesses, such as limited production capacity, suboptimal digital marketing, and low product innovation. The SWOT analysis places the company in Quadrant II (0.20; −0.30), indicating strong internal capabilities but significant external threats. Accordingly, the recommended marketing approach is the Strength–Threat (ST) strategy, which was prioritized through AHP into three main strategies: product quality differentiation, competitiveness enhancement through human resources and technology, and distribution management strengthening. The implementation of these strategies is expected to improve the competitiveness and sustainable export performance of pasteurized blue swimming crab products.